Pemodelan Status Trofik Danau Laut Tawar Aceh Tengah - Saiful Adhar; Erlangga Erlangga; Rachmawati Rusydi; Mainisa Mainisa; Munawwar Khalil; Muliani Muliani; Eva Ayuzar; Muhammad Hatta (Fakultas Teknik, 2022)
The trophic status of Laut Tawar Lake was increasingly leading to an alarming level of degradation. Efforts to anticipate an increase in trophic status require scientific knowledge of the trophic phenomena of the waters empirically. This research examines the trophic status parameters to produce a model of the trophic status of Laut Tawar Lake. The proposed model was a modification of Carlson's Trophic State Index Method. Analysis of the relationship examined the interaction of water clarity (SD) with chlorophyll-a (Chl), Total Suspended Solid, and Total Dissolved Solids, and the interaction of chlorophyll-a with nutrient concentration (TP, TN). Data were analyzed descriptively quantitatively, correlation, and regression. The results showed that the waters of Laut Tawar Lake contain phosphate (TP) 34 µg/L, Total Nitrogen 687 µg/L, chlorophyll-a 10 µg/L, Total Suspended Solid 47 mg/L, Total Dissolved Solid 84 mg/L, and water clarity 4.0 m. The regression test showed that the abundance of phytoplankton (Chl) was affected by nutrient phosphate with the empirical model equation Chl = 0.565 TP – 9.161. Nitrogen nutrients did not partially affect the concentration of chlorophyll-a in the waters of Laut Tawar Lake. Water clarity is influenced by chlorophyll-a and TSS, where TDS has no effect partially. The empirical model obtained is Ln SD = 1.757 – 0.013 Chl – 0.008 TSS. Modification of Carlson's TSI by substituting the two equations obtained the equation TSIdlt = 13.46 + 8.08 ln TP + 0.04 TP + 0.04 TSS. This model simulation gives an estimation rate of 91.06%.